Policy Directions For Animal, Fish And Plant Quarantine Institutions In The Administrative Structure - Rumainur; Henda Hidayat (Arena Hukum, 2022)
This research analyses how the Animal, Fish, and Plant Quarantine Law currently regulates quarantine and its institutions in positive law, the form and position of government institutions referred to in the Indonesian constitutional structure, and the direction of the government’s institutional arrangements is linked to Article 8 of the Quarantine Law. Animals, Fish and Plants in the Indonesian constitutional structure. Therefore, the form of government institution in the quarantine sector based on Article 8 of the Animal, Fish, and Plant Quarantine Law which is in accordance with the Indonesian legal system and constitutional structure is a Government Institution at the Ministry Level, considering the biosecurity function carried out in the implementation of quarantine. This normative legal research is supported by secondary data and analyzed qualitatively. From the results of the research, the government still needs to follow up on the regulation of animal, fish and plant quarantine and its institutions in the Animal, Fish and Plant Quarantine Law by drafting a Government Regulation Draft.